THE FACTORS THAT ARE RELATED TO HYPERTENSION IN ADOLESCENTS IN THE PALU CITY - Sridani, Ni Wayan; Anshary, Alam; Mahfudz; Basir, Muhammad; Mallonggi, Anwar; Syam, Amiruddin; Palutturi, Sukri; Amirudin, Ridwan; Russeng, Syamsiar; Sabir, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension continues to increase from year to year. Where hypertension is not only a problem for adults and the elderly but hypertension is also a problem in. Hypertension in adolescents can continue into adulthood so this will lead to a higher risk of morbidity and mortality. known the factors associated with the incidence of hypertension in the city of Palu. quantitative research with analytic design that used a cross sectional approach, where the risk factors in this study are stress, BMI (Body Mass Index), diet, activity, smoking habits and alcoholic, while the effect is hypertension. showed an independent variable that was significantly related to the incidence of hypertension in adolescents was adolescent nutritional status (BMI) with a value of p <0.05 (p = 0.018), stress level with a value of p <0.05 (p = 0.002), alcoholic with p value <0.05 (p = 0.016), and smoking behavior with a value of p <0.05 (p = 0.05), and dietary habit with a value of p <0.05 (p = 0.002). Conclusion: Factors related to the incidence of hypertension in adolescents are nutritional status (BMI), stress levels, alcoholic and smoking behavior, and dietary habit.